L1 cell adhesion molecule confers radioresistance to ovarian cancer and defines a new cancer stem cell population - Terraneo, Nastassja; Peitzsch, Claudia (Cancers, 2020)
Many solid tumors, including ovarian cancer, contain small populations of cancer stem cells (CSCs). These cells are usually resistant against conventional cancer therapies and play a role in disease recurrence. We demonstrated that the L1 cell adhesion molecule (L1CAM) is a new CSC target in ovarian cancer, triggering radioresistance. Using fluorescence-activated cell sorting, specific cell populations expressing L1CAM alone or in combination with the established CSC marker CD133 were isolated from three ovarian cancer cell lines. Double-positive L1CAM+/CD133+ cells displayed higher spherogenic and clonogenic properties in comparison to L1CAM−/CD133− cells. Furthermore, L1CAM+/CD133+ cells retained highest clonogenic capacity after irradiation and exhibited up-regulation of some CSC-specific genes, enhanced tumor-initiating capacity, self-renewal and higher tumor take rate in nude mice when compared with other cell populations. Superior radioresistance by L1CAM expression was confirmed by deletion of L1CAM using CRISPR-Cas9 technology. Moreover, we found expression signatures associated with epithelial-to-mesenchymal transition phenotype in L1CAM deleted cells. These results indicate that L1CAM in combination with CD133 defines a new cancer cell population of ovarian tumor-initiating cells with the implication of targeting L1CAM as a novel therapeutic approach for ovarian CSCs.